1998
DOI: 10.1109/10.661160
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical analysis on the biological zero problem in laser Doppler flowmetry

Abstract: The biological zero (BZ) problem is a critical issue inherent in laser Doppler flowmetry (LDF). It causes confusion when measuring low tissue blood flows. Many experimental studies have been done on the question of whether the BZ flux should be subtracted from the normally measured flux in various situations. However this problem can only be solved after a proper mathematical analysis. Only then can we clearly define and formulate what flux is truly meaningful in blood perfusion measurement and what movement g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…This residue is possibly due to scatter motions in tissue that are not blood flow, such as random motions of red blood cells and other tissue organelles. A portion of these motions has been dubbed biological zero, because it is observed in freshly sacrificed model organisms, such as with laser Doppler flowmetry (82,83). The present study does not measure the true biological zero, because living tissues will have dynamic signals unrelated to blood flow, although the present study does place an upper bound of ~10% on this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…This residue is possibly due to scatter motions in tissue that are not blood flow, such as random motions of red blood cells and other tissue organelles. A portion of these motions has been dubbed biological zero, because it is observed in freshly sacrificed model organisms, such as with laser Doppler flowmetry (82,83). The present study does not measure the true biological zero, because living tissues will have dynamic signals unrelated to blood flow, although the present study does place an upper bound of ~10% on this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…1), indicating the presence of a ‘biological zero' that needs to be taken into account when using the LSCI technique. The biological zero has been the subject of many studies using laser Doppler flow and has been suggested as consisting of Brownian motions of molecules as well as local redistribution of blood cells within vessels [22,23]. The interpretation and handling of the biological zero is still under debate, but it has been proposed that the underlying mechanism causing the biological zero may not be probed in the same way by the laser Doppler flow and LSCI techniques [24].…”
Section: Discussionmentioning
confidence: 99%
“… 40 How to interpret and handle the biological zero is under debate and needs to be investigated further. 55 , 56 …”
Section: Ldpimentioning
confidence: 99%